Analysis of Plankton Abundance and Status of Water Quality Fish Cultivation “Sawah Tambak” with Overtime System in Kalitengah Subdistrict, Lamongan Regency - Rahayu, Agung Pamuji; Saad, Moch; Fanni, Norma Aprilia (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 1 (2021): ATBES, 2021)
The fish cultivation system in several villages in Kalitengah District uses an overtime system, namely a fish cultivation system that is carried out within 1 year (12 months) without passing rice planting. The research objective was to determine the abundance of plankton and the status of water quality fish cultivation “sawah tambak” with overtime system in Kalitengah District Lamongan. This is a quantitative research using descriptive methods. Based on the plankton abundance value at Station 1,2 and 3, the waters in the overtime system of ponds are in the Eutrooph category, with the abundance value > 12,000 Ind / L. Meanwhile station 4,5, and 6 are included in the Oligotrooph category since its abundance <10,000 Ind / L. The diversity value is within the range of 0.714267-1.823 which include in the category of small diversity and low community stability because the value of 0 <H '<1.5. All stations are in a moderate level of pollution which the diversity index value is within the range of 1 <H '<3. The Dominance Index (D) is in the range 0.212-1.224, Station 1 has a high dominance value because of the dominant species, namely Batrachospermum . Water quality parameters at all stations such asthe temperature ranges between 28.8-34.2 0 C; the pH 8.5-9.2; Dissolved oxygen  4-10.44 mg / l; ammonia 0.009-0.17 mg / l; phosphate ranges from 0.025-2.3 mg / l. From the measurement results, water quality parameters show a good value for the growth of aquatic organisms.